2008
DOI: 10.1007/s10563-008-9049-1
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis by Carbon Dioxide Hydrogenation on Fe-Based Catalysts

Abstract: Impregnated and co-precipitated, promoted and unpromoted, bulk and supported iron catalysts were prepared, characterized, and subjected to hydrogenation of CO 2 at various pressures (1-2 MPa) and temperatures (573-673 K). Potassium, as an important promoter, enhanced the CO 2 uptake and selectivity towards olefins and long-chain hydrocarbons. Al 2 O 3 , when added as a structural promoter during co-precipitation, increased CO 2 conversion as well as selectivity to C 2? hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
162
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 31 publications
5
162
1
4
Order By: Relevance
“…The majority of catalyst for hydrogenation of CO 2 contains Cu as the main component along with different promoters or modifiers (Zn, Zr, Si, Al, Ti, Cr, Ga, Ce, etc.) [50][51][52] and literatures on catalytic CO 2 hydrogenation process containing Fe [53] for methanol synthesis have been found a very few. A proper support not only affects the stabilization and formation of the active phase of the catalyst but it is also able to control the interaction between the promoter and major component.…”
Section: Effect Of Catalysts On Co 2 Hydrogenation To Methanolmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of catalyst for hydrogenation of CO 2 contains Cu as the main component along with different promoters or modifiers (Zn, Zr, Si, Al, Ti, Cr, Ga, Ce, etc.) [50][51][52] and literatures on catalytic CO 2 hydrogenation process containing Fe [53] for methanol synthesis have been found a very few. A proper support not only affects the stabilization and formation of the active phase of the catalyst but it is also able to control the interaction between the promoter and major component.…”
Section: Effect Of Catalysts On Co 2 Hydrogenation To Methanolmentioning
confidence: 99%
“…Other additives such as Zn, Mg, Ru, Zr, and La have also been researched but promoting effect is nearly inappreciable [53,[61][62][63]. Iron based catalysts dispersed on various supports have also been tested extensively and the product distributions are highly dependent on supporting materials [53].…”
Section: Effect Of Catalysts On Co 2 Hydrogenation To Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] While recent studies have indicated that promoted cobalt systemsc an be effectively used for the formation of hydrocarbonsf rom CO 2 , [18] iron'si nherent water-gas shift activity has resulted in it being the main focus for the formation of C 2 + hydrocarbons. [1,10] The authors have recently shown that while an iron-silica catalysth as relatively low activity with selectivityp rimarily to methane, the addition of promoters can shift selectivity towards lower (C 2 -C 4 )o lefins over 40 %. [19] While these results are promising, ad etailedu nderstanding of the kinetics and mass transfer limitations of this process is vital to both optimise catalyst performance and model or scale up the overall process.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of higher alcohols and hydrocarbons through Fischer-Tropschtype reactions leads to a broad range of products, with resulting high costs of separation. However, the production of light olefins (C2-C4) through a Fischer-Tropsch-to-olefin is an industrially interesting process [46,47], for the higher added value of olefins with respect to methanol. It is estimated that methanol synthesis from CO 2 will become commercial within a few years (see later section, in relation to the use of this reaction to import remote RE sources), while light olefins from CO 2 will require more time, because of other competitive possibilities including from biomass [32].…”
Section: Introductionmentioning
confidence: 99%